(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
One of the most pressing challenges in modern linguistics is the necessity to research and develop the discipline of linguoculturology, which analyzes the relationship between language and culture, as well as the expression of language in culture and culture in language. This article analyzes the linguistic features of the Chicano poetry in American literature.